Pomen telesne dejavnosti v odraslem obdobju - Jovičevič, Liza (Šport (Ljubljana), 2023)
This paper presents the importance of physical activity for health in adulthood. Regular physical activity is a key protective factor for the prevention and management of chronic diseases such as cardiovascular disease, type 2 diabetes and many cancers. Physical activity has a positive effect on mental health. It helps to prevent cognitive decline and reduce symptoms of anxiety and depression, as well as maintain a healthy body weight and general well-being. Key messages: physical activity is good for physical and mental health, some physical activity is better than none, but more exercise brings more health benefits, any physical activity counts, and more physical activity and less sitting can benefit everyone.
Keywords: gibanje; odrasli; preventiva; psihofizično zdravje; smernice; šport; telesna aktivnost; zdravje